Carbon Nanofibers Loaded with Carbon Nanotubes and Iron Oxide as Flexible Freestanding Lithium-Ion Battery Anodes. (1st November 2017) - Joshi, Bhavana; Samuel, Edmund; Jo, Hong Seok; Kim, Yong-Il; Park, Sera; Swihart, Mark T.; Yoon, Woo Young; Yoon, Sam S.
Abstract: We demonstrate the fabrication of flexible electrospun carbon nanofibers (CNFs) containing uniformly distributed carbon nanotubes (CNTs) and iron oxide (FeO x ) nanoparticles (NPs) as a composite material for lithium-ion battery (LIB) anodes. The uniform incorporation of CNTs and FeO x NPs within the CNFs was confirmed by transmission electron microscopy. Embedding even a small amount of CNTs (0.1 wt%) in the CNFs increased the LIB performance by a factor of two compared with pure CNFs. The specific capacity was also increased, by 25%, when an iron source (iron (III) acetylacetonate) was added at a concentration of 2 wt%. The FeO x -CNT/CNF electrode maintained a capacity of 1008 mAh∙g −1 at a current density of 100 mA∙g −1 after 100 cycles. Further, the high-performance anode material was freestanding, flexible, and lightweight. This makes it suitable for next-generation LIBs, which must deliver high power over long periods while also being light and flexible.